2020
DOI: 10.3390/cells9051176
|View full text |Cite
|
Sign up to set email alerts
|

Two Birds with One Stone: NFAT1-MDM2 Dual Inhibitors for Cancer Therapy

Abstract: The tumor suppressor p53 is believed to be the mostly studied molecule in modern biomedical research. Although p53 interacts with hundreds of molecules to exert its biological functions, there are only a few modulators regulating its expression and function, with murine double minute 2 (MDM2) playing a key role in this regard. MDM2 also contributes to malignant transformation and cancer development through p53-dependent and -independent mechanisms. There is an increasing interest in developing MDM2 inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 106 publications
0
8
0
Order By: Relevance
“…Several therapeutic agents have been used as an inhibitor of NFAT and MDM2. One of the important targets of NFAT and MDM2 is Lin A [ 100 ]. Qin et al [ 95 ] conducted in an vitro study to investigate Lin A’s role in inhibiting the NFAT-MDM2 pathway.…”
Section: Downstream Regulation Of Signaling Pathways By Natural Productsmentioning
confidence: 99%
“…Several therapeutic agents have been used as an inhibitor of NFAT and MDM2. One of the important targets of NFAT and MDM2 is Lin A [ 100 ]. Qin et al [ 95 ] conducted in an vitro study to investigate Lin A’s role in inhibiting the NFAT-MDM2 pathway.…”
Section: Downstream Regulation Of Signaling Pathways By Natural Productsmentioning
confidence: 99%
“…The NFAT family is expressed in several cancer cell types and plays roles in survival, invasive migration, angiogenesis, and inflammatory microenvironment maintenance ( Ryeom et al, 2008 ). In breast cancer cells, a member of the NFAT family, NFAT1, is ubiquitinated by the E3 ubiquitin ligase murine double minute 2 (MDM2) downstream of Akt and GSK-3 signaling ( Wang et al, 2020b ). Activated NFAT1 promotes the migration and invasion of breast cancer cells in vitro ( Jauliac et al, 2002 ).…”
Section: Irf2bp2 In Cancer Immunomodulationmentioning
confidence: 99%
“…Overexpression of MDM2 and NFAT1 in cancers is correlated with poor prognosis and inhibition of these proteins is a promising targeting strategy for cancer therapy [ 66 ]. NFAT1 modulates MDM2 transcription and activates MDM2 expression, which leads to an increase in p53 inactivation that drives tumourigenesis.…”
Section: Apoptosismentioning
confidence: 99%
“…The Zhang lab initially identified genistein as an MDM2 and NFAT1 dual inhibitor. They expanded their search to develop small molecules with more potent activity, using a computational structure-based screening of natural products that led to the discovery of JapA, LinA and InuA [ 66 ]. A recent report on LinA showed that it is less sensitive in inducing apoptosis in TNBC cells, hence will not be discussed in this review.…”
Section: Apoptosismentioning
confidence: 99%